Dividend Behaviour of Quoted Companies of the Douala Stock Exchange Market, Cameroon - Akume, Daniel Akume; Njimanted, Godfrey; Yakum, Ivan (Archives of Business Research, 2020)
For over sixty years now, finance researchers have concentrated on conducting studies on dividend behaviour as well as its determinants in different countries in the world.Some have exploited the effects of dividend payout on the performance of quoted companies with particular interest on current and previous levels of dividends as it is also the case with the level of profits, most of which give divergent conclusions. It is based on the above that this study was designed to examine the determinants of dividend behaviour ofquoted companies in the Douala Stock Exchange market using the Generalized Method of Moments (GMM) regressiontechniques based on secondary quarterly data from the Douala Stock ExchangeReports. The findings reveals thatearnings per share, the previous level of dividend and capital structure determine the current dividend behaviour in the Douala stock exchange market.While the previous level of dividend serves as a central bench mark when deciding on the dividend policy, increases in earnings per share and/or decrease in debt to equity ratio have potentials of significantly increasing dividend per share. Based on this finding, it is strongly recommended that policy measure by the government or corporate management aimed at providing and controlling a consistent pattern of dividend payment should take the previous level of dividends into consideration and should also pay special attention to earnings per share and capital structure of the listed companies.Therefore the capital structure which must be tilted towards indigenous equity should be put in place to avoid excessive capital flight.